1976
DOI: 10.2136/sssaj1976.03615995004000050043x
|View full text |Cite
|
Sign up to set email alerts
|

The Transfer of Heat and Hydrophobic Substances During Burning

Abstract: Wet and dry sand was tested for water repellency, after burning pine litter (Pinus coulteri D. Don). Four conditions were studied: a burn of 25 min over dry or wet sand and a burn at 5 min over dry or wet sand. The thickest and most intense water‐repellent layer was produced by a 5‐min burn over dry sand. Although organic materials were translocated deeper in the dry sand during the 25‐min burn (down to 4 cm), some of the water repellency was destroyed in the upper 1‐cm layer. In wet sand, water repellency was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(119 citation statements)
references
References 0 publications
4
109
0
3
Order By: Relevance
“…Severe heating of soil breaks down the structures of the inorganic parent materials, destabilizing soil structure (52). Fire creates hydrophobic layers within the soil structure, decreasing water infiltration and increasing soil erosion by water runoff (2,15). Nutrient transformations occur when excessive heat is applied to soils.…”
mentioning
confidence: 99%
“…Severe heating of soil breaks down the structures of the inorganic parent materials, destabilizing soil structure (52). Fire creates hydrophobic layers within the soil structure, decreasing water infiltration and increasing soil erosion by water runoff (2,15). Nutrient transformations occur when excessive heat is applied to soils.…”
mentioning
confidence: 99%
“…This response could be attributed to the different temperature reached on the soil surface during the fire . Laboratory studies showed that fire can enhance SWR at temperatures of 175-200 °C and destroy this feature above 270-600 °C, depending on heat duration and oxygen availability but irrespective of soil type (DeBano et al 1976, Doerr et al 2004, Bryant et al 2005.…”
Section: Post-fire Runoff and Erosion In Andosolsmentioning
confidence: 99%
“…Temperaturas entre 175-207ºC intensifican la repelencia al agua y mayores la destruyen (DeBano et al, 1976). Sin embargo, las temperaturas alcanzadas en el suelo y su duración durante un incendio no suelen ser homogéneas y dependen de varios factores, principalmente de: la distribución, densidad y tipo de vegetación; la cantidad de materia orgánica, textura y humedad del suelo; la topografía, orientación y las condiciones climáticas durante el incendio (Neary et al, 1999).…”
Section: Variabilidad Espacial De La Repelencia Al Agua a Micro Escalaunclassified
“…Estudios de laboratorio muestran que la repelencia al agua se intensifica a temperaturas entre 175 y 270ºC, pero se destruye a temperaturas por encima de 270 hasta 400ºC (según el tiempo de combustión) . Esto es debido a cambios en la estructura de las moléculas orgánicas durante la combustión (Savage et al, 1972), y a que las sustancias orgánicas hidrofóbicas se volatilizan durante el calentamiento desplazándose en profundidad según el gradiente de temperatura, hasta que se condensan a pocos centímetros bajo de la superficie (DeBano et al, 1976). Independientemente de si ha ocurrido un incendio forestal, la repelencia al agua se asocia a la presencia de diversas especies vegetales, pero no se puede asumir que éstas siempre induzcan repelencia al agua ni actúen con la misma intensidad.…”
Section: Introductionunclassified